Scrutinizing online instructional approach: What drives faculty to adopt synchronous virtual classroom - Muluk, Safrul; Habiburrahim, Habiburrahim; Safrul, Muhammad Safwan; Hakim, Lukman; Amiruddin, Amiruddin (Universitas Islam Negeri Banda Aceh, 2023)
The successful implementation of a method appliance can be attributed to the method itself. The matter of synchronous virtual classrooms is influenced by several factors. The adoption of synchronous virtual classrooms by faculty members provides a valuable experience for both students and lecturers. This study aims to identify the triggering factors that motivated faculty members to adopt synchronous virtual classrooms. Additionally, it seeks to examine the challenges faced by students and lecturers in implementing this method. The researchers utilized interviews and literature sources as instruments for data collection. A total of five lecturers were selected as respondents for this research. The criterion for selection was their implementation of this method in their department's courses and their experience with synchronous virtual classrooms. The collected data was thematically analyzed. The results revealed that the main triggering factor for adoption was the Covid-19 pandemic. The challenges faced by students and lecturers were not limited to technological and internet issues but also included a lack of preparation from the faculty. Based on the data analysis and interviews, future research could explore the potential of combining methods to create a more effective approach in different situational conditions.